Предмет: Математика,
автор: dtyedg
x+4/x-4+x-4/x+4=10/3 по подробние пожалуйста
Ответы
Автор ответа:
0
х+4/х-4 (× 3 (х+4))+х-4/х+4 (×3 (х-4))=10/3 (×(х-4)(х+4) -приводим к общему знаменателю
3 (х+4)(х+4)+3 (х-4)(х-4)=10×(х-4)(х+4)
3 (х^2+8х+16)+3 (х^2-8х+16)=10 (х^2-16)
3х^2+32х
3 (х+4)(х+4)+3 (х-4)(х-4)=10×(х-4)(х+4)
3 (х^2+8х+16)+3 (х^2-8х+16)=10 (х^2-16)
3х^2+32х
Похожие вопросы
Предмет: Русский язык,
автор: nikita1583
Предмет: Русский язык,
автор: 5091992
Предмет: Математика,
автор: underisiconiahaw
Предмет: Обществознание,
автор: dzhasi
Предмет: Математика,
автор: симкаек